Directive Speech Acts and Its Response on Japanese Anime “Tensei Shitara Slime Datta Ken” - Intan Elisa Putri Milenia; Firmansyah, Dian Bayu (Chi e Journal of Japanese Learning and Teaching, 2024)
This study aims to classify the directive speech acts used by the character Rimuru Tempest in the anime Tensei Shitara Slime Datta Ken and analyze the responses of interlocutors to these directive speech acts. The research employs a qualitative descriptive approach, with data collected from character dialogues across episodes 1 to 15 of the anime. The data were analyzed and categorized based on Namatame's (1996) directive speech act theory. The findings indicate 24 instances of directive speech acts, categorized into five types: commands (meirei), with 11 occurrences; requests (irai), with 5; prohibitions (kinshi), with 3; permissions (kyoka), with 3; and suggestions (teian), with 2. Additionally, 18 responses to these directives were positive, while 6 were negative. Analysis suggests that the relationship between the speaker and the interlocutor influenced response types. Results also show that the character Rimuru Tempest predominantly used requests (irai) in their directives.